PROTOTYPE AUTOMATIC LIGHTS CONTROL SYSTEM IN THE MOSQUE AREA BASED ON ARDUINO NANO - Sagita Rochman; Bagus Ilham Yunianto (BEST, 2019)
To turn on and turn off lights in the mosque area in general still use a manual system that is to turn off and turn on the lights using a switch located on the wall. Therefore, currently a system that has been designed automatically is needed to control the light of life and the outages of lights based on a predetermined time and based on the detection of human presence, so that the lights will turn on and off automatically at the set time according to needs, namely using Real Time Clock (RTC) and Passive Infrared Receiver (PIR) sensors. The results obtainedin the form of a light controller system in the area of the mosque using DS3231 RTC and Arduino Nano At mega 328P PIR Sensor. At 3:00 and 17:00 the condition of the lights is on and at 05:30 and 21:00 the lights are off. For the measurement of PIR sensor detection distance, the distance of 5 meters of the PIR sensor can still detect the presence of human movements, after 5 meters or even 6 meters of the PIR sensor cannot detect human movement. So that within a distance of 6 meters or more, the toilet lights cannot turn on automatically or turn off.